(untitled) (Universal International Scientific Journal, 2026)
Music therapy in preschool children is an effective tool for developing psychological defense mechanisms, reducing stress, and increasing emotional stability. Musical activities with parents help strengthen children’s mental stability. The thesis highlights the pedagogical and practical significance of music therapy in the context of family psychology.